Arabian nights the book of a thousand nights and a night - Burton, Richard Francis; Harvey, W. W. (William Woodis) (Collector's library editions., 2007)
Full of mischief, valor, ribaldry, and romance, "The Arabian Nights" has enthralled readers for centuries.